MODEL SPEKTRUM RADIASI SURYA DAN SUHU DI DALAM RUMAH PLASTIK (THE SOLAR SPECTRUM AND TEMPERATURE MODEL IN THE PLASTICHOUSE) - . Yushardi; Yonny Kusmaryono; H.M. H. Bintoro; A. H. Tambunan (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2006)
Research has been conducted to develop the solar spectrum and temperature model in the plastic house. The objective of this research is to determine spectrum and temperature optimum in the plastic house. The method was used by field experiment and simulation. Field experiment consist of three treatments. These are first treatment used the plastic Polyethylene (PE) with UV (Ultraviolet) protection (0 %. 6 % and 14 %). The second treament was determined the tilt angle between plastic cover and horizontal planar. The third treatment was flooring by used soil and grass. The expriment reveals that optimum condition for the plastic house that used plastic UV protection 14%, and use grass as the floor. Produce a optimum result in decreasing Tin for 2.9 % in plastic UV 14%, 2.7 % in β= 67o and 5.7 % in using grass as the floor. Spectrum of UV, PAR (Photosintetically Active Radiation) and IR (Infrared) that transmited from PE 14 % plastik 3.0 W/m2. 143.2 W/m2 and 192.8 W/m2 respectively. The other parameter that influence the temperature in plastic house is natural convection coeficient (hi) and ventilation coeficient (hv). For type Hexagonal plastic house hi and hv 1.5 W/m2.C, 50 W/m2.C respectively. For type Tunnel plastic house hi and hv 1.5 W/m2.oC and 55 W/m2.C respectively.